PENGGUNAAN BAHASA INGGRIS DI BAGIAN IZIN TINGGAL DI KANTOR IMIGRASI CILACAP - Febriyanti, Betriana; Puspitasari, Indah; Sari, Rosdiana Puspita (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2021)
The purpose of this study were to find out the use of English in the stay permit section, and to find out the solution to deal with the obstacles of using English in the stay permit section to improve the quality of information services in the immigration office. The Author use several methods such as observation, literature studies, and interviews. The use of English in the stay permit information service is good enough but there are some additions so that the information to be conveyed can be fully conveyed by by giving information about stay permit requirements, immigration stay permit flow, and to fill out the forms. The obstacles and solutions such as limitations in international language, and information. The solution to this problem is to increase vocabulary, often practice listening to the accents of other countries, and using body language. The second is a limitation of information is by finding out in conveying information to provide good and clear information to visitors.